J.J. Pizzuto's fabric science swatch kit - Johnson, Ingrid, 1951-; Sarkar, Ajoy K., ....-; Cohen, Allen C., (Writer on textile industry), ....-; Pizzuto, Joseph J. (Joseph James)., ....- (New York : Fairchild Books, 2016)
J.J. Pizzuto's Fabric Science Swatch Kit, 11th Edition reinforces the study of textiles for students in fashion design, merchandising, interior design, product development and home furnishings. The kit contains 114 (2"x 3") fabric samples, a fabric key, 40 special assignments, heavy-weight sample sheets to mount and analyze fabrics, and a pick glass - all contained in a three-ring binder. The swatches are organized in the order in which they are covered in the text: fibers, yarns, weaves, knits, dyeing, printing and finishes. Swatches represent the types of fabrics currently available to fashion and interior designers in the field, making this resource an excellent addition to any professional library.
Includes bibliographical references and index.
Keywords: Textile fabrics; Textile industry